Oscillation and Nonoscillation of Asymptotically Almost Periodic Half-Linear Difference Equations. (12th June 2013) - Veselý, Michal; Hasil, Petr
Abstract : We analyse half-linear difference equations with asymptotically almost periodic coefficients. Using the adapted Riccati transformation, we prove that these equations are conditionally oscillatory. We explicitly find a constant, determined by the coefficients of a given equation, which is the borderline between the oscillation and the nonoscillation of the equation. We also mention corollaries of our result with several examples.